Covered perforative ulcer of the duodenum with a clinical picture of acute pan-creatitis - S. N. Styazhkina; A. E. Matusevich; M. V. Korniliev; E. V. Babenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
This article is an analysis of a clinical case dedicated to the clinical manifestations and course of a covered duodenal perforative ulcer with a clinical picture of acute pancreatitis.